Penguatan Karakter Peserta Didik Melalui Manajemen Pembelajaran Aqidah Akhlak di MI Masholihul Huda Krapyak Jepara - Subaidi, Subaidi; Mufid, Fathul; Ahmadun, Ahmadun (Pascasarjana IAIN Kudus, 2023)
Strengthening Student Character Through Learning Management Aqidah Akhlak at MI Masholihul Huda Krapyak Jepara.This study aims to explain the strengthening of the character of students through learning management of aqeedah morals at the Masholihul Huda Krapyak Jepara madrasah with a qualitative approach. Collecting data in this study through interviews, observation and documentation. Data analysis techniques are through reduction, display, and verification. In conclusion: 1) the preparation of an implementation plan for aqidah moral learning includes: religious, honest, disciplined behavior, responsibility when interacting with family, friends, ustdaz, and neighbors; 2) the implementation of aqidah moral learning is in accordance with the initial planning, namely: the implementation of religious behavior, honesty, discipline, responsibility when interacting with family, friends, ustadz, and neighbors; 3) the evaluation process is carried out by the head of the madrasa as well as the curriculum sector; 4) Strengthening character education includes religious, honest, disciplined and responsible characters. Penelitian ini bertujuan untuk menjelaskan penguatan karakter peserta didik melalui manajemen pembelajaran aqidah akhlak di madrasah Masholihul Huda Krapyak Jepara dengan pendekatan kualitatif. Pengumpulan data dalam penelitian ini melalui wawancara, pengamatan dan dokumentasi. Teknik analisis datanya melalui reduction, display, dan verification. Kesimpulannya: 1) penyusunan rencana pelaksanaan pembelajaran aqidah akhlak meliputi: karakter relegius, jujur, disiplin, tanggung jawab ketika berinteraksi dengan keluarga, sahabat, ustdaz, dan tetangga; 2) pelaksanaan pembelajaran aqidah akhlak sesuai dengan perencanaan awal yaitu: terimplemetasinya karakterrelegius, jujur, disiplin, tanggung jawab ketika berinteraksi dengan keluarga, sahabat, ustadz, dan tetangga; 3) proses evaluasi dilakukan kepala madrasah serta bidang kurikulum; 4) penguatan karakter meliputi: karakter relegius, jujur, disiplin dan tanggung jawab.